Analyse von Ausführungszeiten durch Integration einer statischen WCET-Analyse mit einer dynamischen Befehlssatzsimulation am Beispiel der TriCore-Architektur - Adelt, Peer

Miniaturized 122 GHz ISM Band FMCW Radar with Micrometer Accuracy - Scherr, Steffen; Göttel, Benjamin; Ayhan, Serdal; Bhutani, Akanksha; Pauli, Mario; Winkler, Wolfgang; Scheytt, Christoph; Zwick, Thomas (European Microwave Week 2015)
In this paper, a miniaturized 122 GHz ISM band FMCW radar is used to achieve micrometer accuracy. The radar consists of a SiGe single chip radar sensor and LCP off-chip antennas. The antennas are integrated in a QFN package. To increase the gain of the radar, an additional lens is used. A combined frequency and phase evaluation algorithm provides micrometer accuracy. The influence of the lens phase center on the beat frequency phase and hence, the overall accuracy is shown. Furthermore, accuracy limitations of the radar system over larger measurement distances are investigated. Accuracies of 200 μm and 2 μm are achieved over a distance of 1.9 m and 5 mm, respectively.

On the Correlation of HW Faults and SW Errors - Müller, Wolfgang; Wu, Liang; Scheytt, Christoph; Becker, Markus; Schoenberg, Sven (Proceedings of the 1st International Workshop on Resiliency in Embedded Electronic Systems (REES 2014))

Integrated Planar Antenna Designs and Technologies for Millimeter-Wave Applications - Wang, Ruoyu
This thesis investigates the design and realization of integrated planar antennas for millimeter-wave applications. The state-of-the-art antenna integration and packaging technologies are extensively studied, and an antenna design flow is proposed. A number of integrated antenna designs by applying different integration approaches and technologies, i.e. on printed circuit board (PCB), on-chip and in Benzocyclobutene (BCB) above-wafer process, are presented. The designs target not only high performance, but also the practical considerations of low-cost, feasibility, better reliability, and good reproducibility. They cover the industrial, medical, and scientific (ISM) bands of 60 GHz, 122 GHz, and 245 GHz in the millimeter-wave range with outstanding performance in a low-cost fashion by applying innovative, appropriate integration methods and sophisticated design. By applying the localized backside etching (LBE) process the presented on-chip antennas achieve measured peak gains of 6–8.4 dBi for above 100 GHz applications with simulated efficiencies of 54–75%. These figures are comparable to that of on-board or in-package antennas. To the best of my knowledge, the achieved gain of 7.5–8.4 dBi in the band of 124–134 GHz for the 130 GHz on-chip double folded dipole antenna is the highest reported result to date for planar on-chip antennas based on low-resistivity silicon technologies. System demonstrators with integrated antennas are realized and measured. The 60 GHz demonstrator with on-PCB differential bunny-ear antenna and a novel bond-wire compensation scheme achieves a data rate of 3.6 Gbit/s over a 15-meter distance, which was the best reported analog front-end without beamforming function in silicon technology regarding both the data rate and transmission distance at the time of its publication. A 245 GHz single-channel transmitter and a single-channel receiver with integrated on-chip antennas are also demonstrated. An effective isotropic radiated power (EIRP) of 7–8 dBm is achieved for the transmitter, which is the highest reported value at 245 GHz for a SiGe transmitter with a single antenna so far. Furthermore, the receiver has the highest reported integration level for any 245 GHz SiGe receiver. A 245 GHz 4-channel-transmitter array with integrated on-chip antenna array is also realized to achieve spatial power combining, which offers 11 dB higher EIRP than a single-channel transmitter. From the presented results of the thesis it is feasible to realize high performance integrated planar antennas in the entire millimeter-wave range and beyond in a cost-effective fashion.

System Design Considerations for a PSSS transceiver for 100Gbps wireless communication with emphasis on mixed Signal implementation - Javed, Abdul Rehman; Scheytt, Christoph; KrishneGowda, Karthik; Kraemer, Rolf (Wireless and Microwave Technology Conference (WAMICON))
Parallel Sequence Spread Spectrum (PSSS) is a physical layer (PHY) baseband technology which is gaining interest for both wireless and wired multi-gigabit communication systems. PSSS is well suited for mixed signal transceiver implementation including channel equalization and allows for a reduction in power dissipation by avoiding high speed data converters. The architecture of a mixed signal baseband processor for 100 Gbps wireless communication is described that reduces the implementation complexity and results in a consequent reduction in power dissipation and chip area.

System Design and Simulation of a PSSS Based Mixed Signal Transceiver for a 20 Gbps Bandwidth Limited Communication Link - Javed, Abdul Rehman; Scheytt, Christoph (1st URSI Atlantic Radio Science Conference (URSI AT-RASC 2015))
Parallel Sequence Spread Spectrum (PSSS) is a physical layer baseband technology wherein parallel data streams are transmitted simultaneously by spreading them using orthogonal codes. PSSS was selected for the wireless sensor network standard IEEE802.15.4-2006 to increase data rate and improve performance in fading channels for frequency bands below 1 GHz. Since then it has gained interest for both wireless and wired communication links.

Mixed-Signal Baseband Processing for 100 Gbit/s Communications - Scheytt, Christoph; Javed, Abdul Rehman (European Microwave Week 2015)

Mixed-mode Baseband for 100 Gbit/s Wireless Communications - Javed, Abdul Rehman; Scheytt, Christoph; Kraemer, Rolf; Messinger, Tobias; Kallfass, Ingmar

PSSS baseband receiver circuit design - Javed, Abdul Rehman

100 Gigabit pro Sekunde und mehr für das drahtlose Hochgeschwindigkeits-Internet - Scheytt, Christoph; Javed, Abdul Rehman (ForschungsForum Paderborn)

Concept for a hierarchical load control for domestic appliances in smart grids - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (2014 International Conference on Advances in Green Energy (ICAGE))

Hierarchisches Optimierungskonzept für die Laststeuerung von Haushaltsgeräten - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (ETG-Fachtagung "Von Smart Grids zu Smart Markets")
Haushaltsgeräte aus der Klasse der "Weißen Ware" tragen mit etwa einem Drittel ($34,2%$ \citeBDEW2013) zum privaten Energieverbrauch bei. Diese Veröffentlichung präsentiert eine Struktur und die dafür notwendige optimale Betriebsstrategie für Weiße Ware in einer Umgebung mit Strompreisen, die wegen der Volatilität der Regenerativen Energien stark fluktuieren. Das vorgeschlagene Konzept nutzt dafür ein dezentrales Energiemanagementsystem, das über drei Hierarchieebenen verteilt ist: die Geräteebene, die Haushaltsebene und die Ortsnetzebene. Auf der Geräteebene nutzt dieses Konzept zusätzlich Betriebsflexibilitäten der Haushaltsgeräte aus.
Keywords: Energy management; hybrid energy storage system; self-optimization; multi-objective optimization; adaptive systems; pareto set; SFB614-D1; SFB614-D2; LEA-Publikation; Eigene

Global Identification of a Low-Order Lumped-Parameter Thermal Network for Permanent Magnet Synchronous Motors - Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Energy Conversion)

An open-loop operation strategy for induction motors considering iron losses and saturation effects in automotive applications - Wallscheid, Oliver; Meyer, Michael; Böcker, Joachim (2015 IEEE 11th International Conference on Power Electronics and Drive Systems)

Design and Identification of a Lumped-Parameter Thermal Network for Permanent Magnet Synchronous Motors Based on Heat Transfer Theory and Particle Swarm Optimisation - Wallscheid, Oliver; Böcker, Joachim (European Conference on Power Electronics and Applications (EPE))

Design and Empirical Identification of a Lumped Parameter Thermal Network for Permanent Magnet Synchronous Motors with Physically Motivated Constraints - Wallscheid, Oliver; Böcker, Joachim (IEEE International Electric Machines and Drives Conference (IEMDC))

Today's Relevance of Digital Control in Server- and Telecom Power Supplies - Schafmeister, Frank; Grote, Tobias; Figge, Heiko (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Adaptable AC Input Phase Switching - Ide, Peter; Schafmeister, Frank; Richter, Jörg; Pour, Barzin; Spesser, Daniel; Herke, Dietmar

Resistorless Precharging - Hufnagel, Michael; Schafmeister, Frank

Co-simulation of an interior permanent magnet synchronous motor with segmented rotor structure - Schulte, Christoph; Böcker, Joachim (IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society)

Switching strategy for Direct Model Predictive Control in power converter and drive applications with high switching frequency - Leuer, Michael; Böcker, Joachim (2015 6th International Conference on Automation, Robotics and Applications (ICARA))

Operating electrical high speed drives with pulse patterns of specific harmonic content - Peter, Klaus; Böcker, Joachim (2015 IEEE Energy Conversion Congress and Exposition (ECCE))

Self-optimizing Model Predictive Direct Torque Control for electrical drives - Leuer, Michael; Böcker, Joachim (2015 IEEE 24th International Symposium on Industrial Electronics (ISIE))

3D analytical model for estimation of eddy currentlosses in the magnets of IPM machine considering the reaction field of the induced eddy currents - Paradkar, Milind; Böcker, Joachim (2015 IEEE Energy Conversion Congress and Exposition (ECCE))

Voltage-Sequence-Control-Based High-Current Rectifier System - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (IEEE Transactions on Industry Applications)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

A comparison of on-board chargers for electric vehicles with variable DC-link voltage - Bolte, Sven; Speerschneider, Alexander; Fröhleke, Norbert; Böcker, Joachim (2015 IEEE International Conference on Smart Energy Grid Engineering (SEGE))

DCM detection for on-line adaption of control parameters for totem-pole PFC rectifier - Henkenius, Carsten; Fröhleke, Norbert; Böcker, Joachim; Figge, Heiko; Grote, Tobias (2015 IEEE International Conference on Industrial Technology (ICIT))

PFC-control for improved inductor utilization - Keuck, Lukas; Fröhleke, N.; Böcker, Joachim; Ziessler, A. (2015 17th European Conference on Power Electronics and Applications (EPE'15 ECCE-Europe))

Analysis of industrial microgrid power curves based on the theory of stochastic variables for control system development and component sizing - Vogt, T.; Keuck, L.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Conference on Advances in Green Energy (ICAGE))

Comparison of PWM AC chopper topologies - Hagemeyer, Marc; Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Averberg, Andreas; Wallmeier, Peter (IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society)

Voltage utilization in Model Predictive Control for IPMSM - Leuer, Michael; Böcker, Joachim (2014 IEEE International Conference on Power Electronics, Drives and Energy Systems (PEDES))

Neuro control of a PFC rectifier for harmonic reduction at partial loads - Keuck, Lukas; Hemmelgarn, F.; Fröhleke, N.; Böcker, Joachim; Vohrmann, M.; Jungeblut, T.; Rückert, U. (2014 International Conference on Advances in Green Energy (ICAGE))

Wirkungsgradoptimale Regelung von permanenterregten Synchronmotoren in automobilen Traktionsanwendungen unter Berücksichtigung der magnetischen Sättigung - Peters, W.

High Power Factor High-Current Variable-Voltage Rectifiers - Solanki, J.

A process for the preparation of a population inversion in a quantum system using multi-pulse excitation - Zrenner, Artur; Förstner, Jens; Mantei, Dirk
Die Erfindung betrifft ein Verfahren zur Präparation einer Besetzungsinversion in einem Quantensystem (Q) mittels Mehrpulsanregung, wobei ein Quantensystem (Q) umfassend wenigstens einen Quantenpunkt mit zwei orthogonalen Zuständen (/X>, /Y>), insbesondere die mit zueinander orthogonalen Polarisationen (P1, P2) optisch anregbar sind, mit einem ersten Laserpuls (L1) beleuchtet wird, welcher zur resonanten Anregung des ersten (/Y>) der zwei Zustände (/X>, /Y>) eingestellt wird und zeitlich nachfolgend mit einem zweiten Laserpuls (L2) beleuchtet wird, der zur resonanten Anregung des zweiten (/X>) der zwei Zustände (/X>, /Y>) eingestellt wird.
Keywords: tet_topic_qd

Technology Enhanced Emotion Expression Learning - Chen, Mei-Hua; Chen, Wei-Fan; Ku, Lun-Wei (Proceedings of the sixth joint Foreign Language Education and Technology Conference (FLEAT VI))

Symmetry exploiting control of hybrid mechanical systems - Flaßkamp, K.; Hage-Packhäuser, S.; Ober-Blöbaum, Sina (Journal of Computational Dynamics)

High order variational integrators in the optimal control of mechanical systems - Campos, C. M.; Ober-Blöbaum, Sina; Trélat, E. (Discrete and Continuous Dynamical Systems)

Asymptotic spectral gap and Weyl law for Ruelle resonances of open partially expanding maps - ARNOLDI, JEAN FRANCOIS; FAURE, FRÉDÉRIC; Weich, Tobias (Ergodic Theory and Dynamical Systems)
We consider a simple model of an open partially expanding map. Its trapped set ${\mathcal{K}}$ in phase space is a fractal set. We first show that there is a well-defined discrete spectrum of Ruelle resonances which describes the asymptotic of correlation functions for large time and which is parametrized by the Fourier component $\unicode[STIX]{x1D708}$ in the neutral direction of the dynamics. We introduce a specific hypothesis on the dynamics that we call ‘minimal captivity’. This hypothesis is stable under perturbations and means that the dynamics is univalued in a neighborhood of ${\mathcal{K}}$ . Under this hypothesis we show the existence of an asymptotic spectral gap and a fractal Weyl law for the upper bound of density of Ruelle resonances in the semiclassical limit $\unicode[STIX]{x1D708}→ ∞$ . Some numerical computations with the truncated Gauss map and Bowen–Series maps illustrate these results.
Keywords: Applied Mathematics; General Mathematics

Resonance Chains and Geometric Limits on Schottky Surfaces - Weich, Tobias (Communications in Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Multi-Objective Storage Operating Strategy for Industrial Microgrids - Vogt, Thorsten; Fröhleke, Norbert; Böcker, Joachim; Kempen, Stefan (German-Korean Symposium on Power Electronics)

Mehrziel-Speicherbetriebsstrategie für industrielle Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S.

Gibbs measures on permutations over one-dimensional discrete point sets - Richthammer, Thomas; Biskup, Marek (Communications in Mathematical Physics)
We consider Gibbs distributions on permutations of a locally finite infinite set X⊂R, where a permutation σ of X is assigned (formal) energy ∑x∈XV(σ(x)−x). This is motivated by Feynman’s path representation of the quantum Bose gas; the choice X:=Z and V(x):=αx2 is of principal interest. Under suitable regularity conditions on the set X and the potential V, we establish existence and a full classification of the infinite-volume Gibbs measures for this problem, including a result on the number of infinite cycles of typical permutations. Unlike earlier results, our conclusions are not limited to small densities and/or high temperatures.

The rate of convergence to stationarity for M/G/1 models with admission controls via coupling - Kolb, Martin; Stadje, Wolfgang; Wübker, Achim (Stochastic Models)
We study the workload processes of two M/G/1 queueing systems with restricted capacity: in Model 1 any service requirement that would exceed a certain capacity threshold is truncated; in Model 2 new arrivals do not enter the system if they have to wait more than a fixed threshold time in line. For Model 1 we obtain several results concerning the rate of convergence to equilibrium. In particular, we derive uniform bounds for geometric ergodicity with respect to certain subclasses. For Model 2 geometric ergodicity follows from the finiteness of the moment-generating function of the service time distribution. We derive bounds for the convergence rates in special cases. The proofs use the coupling method.

Local asymptotics for the area of random walk excursions - Kolb, Martin; Denisov, Denis; Wachtel, Vitali (Journal of the London Mathematical Society)
We prove a local limit theorem for the area of the positive excursion of random walks with zero mean and finite variance. Our main result complements previous work of Caravenna and Chaumont; Sohier, as well as Kim and Pittel.

Towards Vandalism Detection in Knowledge Bases - Heindorf, Stefan; Potthast, Martin; Stein, Benno; Engels, Gregor (SIGIR)

Silicon photonics 90° optical hybrid design for coherent receivers - Gudyriev, Sergiy; Scheytt, Christoph (Kleinheubacher Tagung 2015)
The recent rapid development of silicon photonics technology has spurred the process of on-chip integration of all kinds of opto-electronic components. One of the most common components of such type is the opto-electrical receiver. The monolithic implementation of the receiver could potentially have lower power consumption, higher sensitivity and bandwidth due to very short diode to amplifier connection length, which has very low parasitic capacitance and series resistance. The SiGe photodiode itself is also very compact, thus lowering the junction capacitance and improving its bandwidth. Among the different optical communication systems, coherent transmission lately received a lot of attention due to the rising requirements of the optical link capacity, and it was shown that this particular approach could benefit greatly from the monolithic integration, since the major component required for the demodulation on the receiver side – 90° optical hybrid – could be implemented fully passive and directly on the same chip as the receiver itself, together with digital post-processing circuitry. Despite the initial complexity of the modulation scheme, advanced silicon photonics components like this optical hybrid could make coherent transmission attractive even for short-range optical links. I would like to present the actual designs, implementation and measurement results of 90° fully passive optical hybrids, implemented in the IHP SG25PIC (passive photonics IC) technology. One of the designs is based on 4x4 multimode interferometer (MMI). The other one is based on two separate 2x2 MMIs with additional delay element. The final designs didn’t require any additional tuning after fabrication and have shown sufficient precision and performance for a coherent system design. The results of this work were later used for the design of monolithic coherent receiver.

Lecture meets laboratory experimental experiences for large audiences: Results of a first implementation and recommendation - Nofen, Barbara; Temmen, Katrin (2015 IEEE Global Engineering Education Conference (EDUCON))

Implementation of Hybrid Filter for 12-Pulse Thyristor Rectifier Supplying High-Current Variable-Voltage DC Load - Solanki, J.; Fröhleke, N.; Böcker, Joachim

Polarization-Dependent Loss: New Definition and Measurement Techniques - Noé, Reinhold; Koch, Benjamin; Sandel, David; Mirvoda, Vitali (JOURNAL OF LIGHTWAVE TECHNOLOGY)